KONTROL DAN MONITORING OTOMATIS RUMAH KACA UNTUK BUAH STRAWBERRY - Widya Nuraeni; Eka Dwi Nurcahya; Didik Riyanto (Universitas Muhammadiyah Ponorogo, 2019)
Strawberry fruit is one commodity that has the potential to be commercially developed, because strawberries have high economic value. However, strawberries in Indonesia at this time only lead to the level of quantity of production by holding land expansion, not yet leading to the level of quality and handling of strawberries after harvest. Greenhouse is a building made of glass or plastic which can be used as a place for cultivation of plants. Greenhouses are designed so that the cultivated plants obtain optimal conditions in the growth process. The system inside the greenhouse can be controlled automatically to reduce the room temperature so that plants can grow optimally. Automatic greenhouse control and monitoring for strawberry fruit is designed with a building ratio of 1: 25cm from its original size and can accommodate strawberry fruit plants in 2 small polybags used as research samples. This control and monitoring system starts from the input process which is derived from the DHT11 temperature sensor and the YL69 soil moisture sensor. Temperature sensors can read greenhouse conditions by getting a 5V DC voltage from Arduino Uno, as well as the YL69 sensor. The results obtained are the temperature sensor can read the temperature and conditions in the greenhouse then displayed on the 16x2 character LCD screen and the YL69 soil moisture sensor can read the water content below 70% which will then turn on the water pump automatically and provide notification through the telegram application with the help of Wi-Fi module ESP8266.